Pregnancy outcome after hysteroscopic myomectomy. (February 2014) - Litta, Pietro; Conte, Lorena; De Marchi, Francesca; Saccardi, Carlo; Angioni, Stefano
Abstract The objective of this longitudinal retrospective study was to evaluate the influence of submucosal myomas on pregnancy outcome in infertile patients after resectoscopic myomectomy. One-hundred and four women with at least a 1-year-long history of infertility and the presence of submucosal myomas as the only cause of infertility were selected after surgical treatment. Pregnancy, delivery and abortion rates were investigated. Patients were divided into three groups according to the myoma classification (G0, G1 and G2). Gestational outcomes were analyzed in the three groups correlated by size, location and number of fibroids. The total pregnancy rate was 85.8% and no difference was shown regarding myoma classification (G0 82.05% versus G1 87.09% versus G2 88.2%; p = ns). Pregnancy and delivery rates were not significantly related to the number, localization or diameter of the fibroids. The abortion rate was not statistically influenced by myoma type, but it was significantly interelated with myomas situated in the anterior uterine wall (p = 0.03). Pre-term delivery was significantly influenced by myomas localized in the fundic wall (p = 0.02). Caesarean section rates were not affected by the characteristics of the myomas. Our results support the idea that resectoscopic myomectomy should be offered to infertile women who wish to become pregnant independently of their localization and number.